Effects of Bank and Non Bank Institution Credit on Small and Medium Size Enterprise in Cameroon - Dr Takoutio Feudjio Virginie (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This study examined the effect of bank and non-bank institution credit on the growth of Small and medium size enterprises in Cameroon. The study made use of secondary data collected by the National Institute of Statistics in Cameroon, which is the Cameroon Enterprise Survey data, 2016. This data has a total number of 361 enterprises. The study sampled three distinct regions of Cameroon, the Center Region, Littoral and the West Region with 149, 143 and 69 enterprises respectively. The Binary Logit regression model was employed to investigate the effect of access to credit on SMEs growth. The results revealed that access to credit from banking institution decreases the likelihood of a SMEs growth by 0.0020 units while the access to credit from non-banking financial institutions increase the likelihood of a SMEs growth. To make the model stronger, control variables like age of the enterprise and legal status where included in the model. The resultant count R square which is the predicting power of our model stood at 76%, meaning the model was a good model as more than 50% of changes in the dependent variable SMEs growth (sales) are explained by the variations in the independent variables specified in the model. From the results, the policy recommendation is that the Banking institutions should readjust their lending system to be more friendly to SMEs in Cameroon while encouraging the SMEs to focus on getting more loans from the NBFIs suppliers